Description of Discipline of Learning Citizens in the Skills of Hand Crafts Skills in PKBM Diknaker Pesisir Selatan - Finta Wulandari; Syuraini Syuraini (Universitas Negeri Padang, 2019)
This research is motivated by the high learning outcomes obtained by citizens learning in the craft skills training program at PKBM Diknaker. Researchers suspect that the high learning outcomes obtained by learning citizens, are influenced by the high discipline owned by citizens learning handicraft skills in PKBM Diknaker. This can be seen from the discipline of citizens learning mental attitudes, understandings and behavioral attitudes. This study aims to illustrate the discipline of citizens learning in the craft skills training program at PKBM Diknaker. This type of research is quantitative descriptive research. The population in this study totaling 20 people. The sampling technique used was a census, all populations were sampled 20 people. Data collection techniques using a questionnaire. While the data analysis technique uses the percentage formula. From the results of the study it was found that: the discipline of learning citizens towards mental attitude was categorized as good, understanding was categorized as good, behavior was categorized as good. Based on this research it’s recommended that the manager to maintaning and improve the dicipline and motivate resident for develop the skills of residents.Keywords: Discipline, Learning Outcomes